IMPLEMENTATION OF THE UTAUT MODEL TO ASSESS THE ACCEPTANCE OF WEB-BASED MULTIMODAL LEARNING MEDIA AMONG TEACHERS - Lestari, Williyanti; Abidin, Yunus; Trie Kurniawan, Dede (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This research aims to implement the UTAUT (Unified Theory of Acceptance and Use of Technology) Model in assessing the acceptance of web-based multimodal learning media among teachers. Web- based multimodal learning media is a platform that integrates various multimedia elements such as text, images, audio and video, which can be accessed via the internet. The research method used is a survey with the UTAUT questionnaire which has been adapted to the context of teacher use of learning media. Research participants are teachers who have utilized web-based multimodal learning media in their teaching activities. The data obtained were analyzed using descriptive statistics and regression analysis. The research results show that the UTAUT model is effective for evaluating the acceptance of web-based multimodal learning media, with the main factors influencing acceptance being perceived usefulness, ease of use, sustainability, and social influence. Apart from that, previous experience and technological conditions also play a role in the acceptance of this media. Based on these findings, it can be concluded that web-based multimodal learning media has great potential to increase learning effectiveness among teachers, and the results of this research provide important guidelines for further development of this learning media so that it is more accepted and used optimally.